2010
DOI: 10.1086/649794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultraviolet C for Disinfection of Endocavitary Ultrasound Transducers Persistently Contaminated despite Probe Covers

Abstract: Endocavitary ultrasound probes may carry pathogens after removal of covers under routine conditions. A disinfection procedure consisting of cleaning with a disinfectant-impregnated towel followed by disinfection with UVC may provide a useful method for disinfecting endocavitary ultrasound probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 17 publications
(15 reference statements)
4
60
0
Order By: Relevance
“…We observed a 2.2% rate of HR-HPV contamination of probes (1.8% before use and 2.5% after use). This result is in agreement with the results observed by Kac G et al [10], who reported 8.2% (95% CI, 4.0%–15.5%) of vaginal-rectal ultrasound probe covers contaminated with HPV, and 0.9% (3/336) contaminated after retrieval of the probe cover, but before low level disinfection (LLD). In a recent publication, Ma ST detects a proportion of 7.5% probes positive for HPV DNA [13].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We observed a 2.2% rate of HR-HPV contamination of probes (1.8% before use and 2.5% after use). This result is in agreement with the results observed by Kac G et al [10], who reported 8.2% (95% CI, 4.0%–15.5%) of vaginal-rectal ultrasound probe covers contaminated with HPV, and 0.9% (3/336) contaminated after retrieval of the probe cover, but before low level disinfection (LLD). In a recent publication, Ma ST detects a proportion of 7.5% probes positive for HPV DNA [13].…”
Section: Resultssupporting
confidence: 93%
“…The close contact between the probe and the cervix uteri or vaginal wall may represent a potential vector for sexual transmitted infections, such as HPV. In 2010 Kac noticed HPV contamination of endovaginal and endorectal ultrasound probes, despite usage of specific probe covers [10]. French national disinfection guidelines classify covered endovaginal ultrasound probes as non-critical devices and therefore undergo low level disinfection with products such as quaternary ammonium compounds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, HPV was detected in six pre-examination samples. This study, as well as others, showed that a large amount of ultrasound probes were contaminated with high-risk HPV [57][58][59][60]. As discussed, most clinical disinfectants are inadequate to neutralize HPV.…”
Section: Potential Routes and Evidence Of Non-sexual Transmissionsupporting
confidence: 60%
“…70,80,89,92,121,122 There is evidence from in vitro studies that some NTD systems are more susceptible to organic soiling than others. For example, H 2 O 2 vapour systems are more able to penetrate increasing levels of organic soiling than aHP.…”
Section: Selecting Validating and Regulating Ntd Systemsmentioning
confidence: 99%